AN INVESTIGATION OF STUDENTS’ PERCEPTION TOWARD LISTENING COMPREHENSION DIFFICULTIES AND TOP-DOWN LISTENING STRATEGY - Rika Lestari; Ikhsanudin Ikhsanudin; Yohannes Gatot Sutapa Yuliana (ICoTE Proceedings, 2019)
The main purpose of conducting this research is to investigate students’ perception toward listening comprehension difficulties and the use of Top-down listening strategy in listening class of the ninth grade students of SMPN 13 Pontianak in the year 2018-2019. It also investigated the correlation between students’ listening difficulties and strategy usage. The method of this research is a cross-sectional survey. The data were collected by using a questionnaire, continuous Likert-scale. Then, the data collected from the questionnaire was analyzed by using descriptive statistical analysis to present the items frequency, mean, and standard deviation. The population of this research is all of the ninth grade students at SMPN 13 Pontianak. The total population is 333 students from 9 classes. While the participants are 168 selected through representative stratified random. The findings showed that accent, pronunciation, the speed of speech, lack of vocabulary, the complex grammatical structure, basic background knowledge,  lack of concentration, bad quality of recording were the major difficulties encountered by the ninth grade students in SMPN 13 Pontianak. The development of listening skill to the learners must be intensified in language learning because listening is critical and important not only as a receptive skill but also as a tool needed for the development of spoken language ability.